Bahasa Rupa pada Pakaian Penghulu Minangkabau - ., Ariusmedi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2011)
This article is a summary of research studying Minangkabau traditional costumes, with focus on the costume of penghulu (head of tribe), which has symbols in it. The penghulu costume as a kind of visual language reflects the position of the wearer in the society, in correlation with his title, as a carrier of the Minangkabau traditional norms. Key words: Minangkabau penghulu costume, visual language